Staphylococcus aureus and autoimmune uveitis reactivation in childhood: a possible correlation? - Zavota Laura; Manzotti Francesca; Kamberi Erilda; Mora Paolo; Orsoni Jelka G (BMC, 2009)
Abstract The role of infectious agents in autoimmune diseases has been the subject of several studies and is still under investigation. Here a paediatric case series of autoimmune uveitis is reported. An exacerbation of the ocular inflammation occurred in concomitance with nasal colonisation by Staphylococcus aureus.